El renacimiento de la electroquímica - Leidinger, Walter; Weber, Rainer (Pontificia Universidad Católica del Perú, 2018)
Germany has decided to switch its entire energy supply to renewables in a transition that they have termed as “Energiewende”. A rethinking of industrial production, especially of the chemical production, is the consequence.Organic electrochemistry is thus celebrating a renaissance, since it allows the coupling of renewable energies and chemical production. A highly efficient, sustainable “green chemistry“ with CO2 as the future raw material basis is possible.

La transición energética, o Energiewende, que ha propuesto Alemania para su futuro abastecimiento energético con energías renovables conlleva un replanteamiento de la producción industrial, especialmente para su industria química.La Electroquímica orgánica celebra, por ello, un renacimiento dado que permite el acoplamiento entre una producción energética a partir de energías renovables y la producción química, y permite, de este modo, una “química verde” de alta eficiencia y sostenibilidad cuya materia prima futura sea CO2.
The renaissance of electrochemistry
Keywords: Energiewende; Transición energética; Energías renovables; Electroquímica; https://purl.org/pe-repo/ocde/ford#1.04.00